Between the Regional and the National Level: East Asian Security Dynamics and Abe's Legacy on Japan's Civil-Military Relations - Pratama, Januar Aditya; Sudirman, Arfin (Global: Jurnal Politik Internasional, 2022)
Since Prime Minister Shinzo Abe began his second term in office in 2012, there have been significant changes in the position of the Japanese military in the country's hierarchy. The change that was occurred almost simultaneously with the increasing threat in the East Asian region since the end of the Cold War, made as a pretext by PM Abe to reform Japan's defence structure. Based on the two factors, this study seeks to find out how the influence of the pattern of relations between countries in the East Asian security complex can affect the pattern of Japanese civil-military relations. This effort was carried out through the framework of the Huntingtonian civil-military relationship, which was concerned with civil ideology, formal and informal influences, and forms of civil control within the state, supported by the complex concept of security from the Copenhagen School which was concerned with patterns of relations and balance of power. It was found that the increasing instability of the East Asian security complex had prompted PM Abe's Japanese decision-makers to change their civil-military relations, either directly from the perception of the political elites themselves, or indirectly through encouragement from the United States. An increase in regional instability itself will encourage the state to participate in increasing military power, including by making changes to its civil-military relations so that defence policies are more targeted in order to ensure their sovereignty and territorial integrity.